Photoelectrochemical properties of Cu-Ga-Se photocathodes with compositions ranging from CuGaSe2 to CuGa3Se5. (20th January 2021) - Mahmoudi, Behzad; Caddeo, Francesco; Lindenberg, Titus; Schneider, Thomas; Hölscher, Torsten; Scheer, Roland; Maijenburg, A. Wouter
Abstract: Cu-Ga-Se chalcopyrite structures with a band gap of 1.68 eV (CuGaSe2 ) to 1.85 eV (CuGa3 Se5 ) are considered to be promising materials to be used as the photocathode in a tandem photoelectrochemical (PEC) water splitting configuration. Therefore, we prepared polycrystalline Cu-Ga-Se films with different compositions ranging from Cu-poor CuGaSe2 (Cu/Ga = 0.85) to extremely Cu-poor CuGa3 Se5 (Cu/Ga = 0.33) and investigated the effect of the Cu/Ga ratio on the crystal structure, morphology and PEC performance of the films. Without any surface treatment or formation of a p-n junction, we report remarkable saturated photocurrent densities of -19.0 and -12.1 mA/cm 2 (measured at -0.40 V vs. RHE) for our films with Cu/Ga = 0.85 and Cu/Ga = 0.33, respectively, using an LED-based solar simulator. These outstanding results cover 86% and 68% of the maximum theoretical photocurrents for materials with a band gap of 1.68 eV and 1.85 eV, respectively. Furthermore, electrochemical impedance spectroscopy (EIS) confirmed that the obtained difference in onset potential (270 mV) between these two films was in agreement with the obtained difference in flat-band potential (290 mV). Graphical abstract: Image, graphical abstract